Characteristics of Social Network Gamers: Results of an Online Survey - Geisel, Olga; Panneck, Patricia; Stickel, Anna; Schneider, Michael; Müller, Christian A. (Frontiers in Psychiatry, 2015)
Current research on internet addiction (IA) reported moderate to high prevalence rates of IA and comorbid psychiatric symptoms in users of social networking sites (SNS) and online role-playing games. The aim of this study was to characterise adult users of an internet multiplayer strategy game within a SNS. Therefore, we conducted an exploratory study using an online survey to assess sociodemographic variables, psychopathology and the rate of IA in a sample of adult social network gamers by Young´s Internet Addiction Test (IAT), the Toronto Alexithymia Scale (TAS), the Beck Depression Inventory II (BDI-II), the Symptom Checklist-90-R (SCL-90-R) and the WHO Quality of Life-BREF (WHOQOL-BREF). All participants were listed gamers of “combat zone” in the SNS “Facebook”. In the IAT analysis, 16.2 % of the participants (n = 60) were categorized as subjects with IA and 19.5 % (n = 72) fulfilled the criteria for alexithymia. Comparing study participants with and without IA, the IA group had significantly more subjects with alexithymia, reported more depressive symptoms, and showed poorer quality of life. These findings suggest that social network gaming might also be associated with maladaptive patterns of internet use. Furthermore, a relationship between IA, alexithymia and depressive symptoms was found that needs to be elucidated by future studies.